Affect and Creativity at Work - Amabile, Teresa M.; Barsade, Sigal G.; Mueller, Jennifer S.; Staw, Barry M. (Administrative Science Quarterly, 2005)
This study explored how affect relates to creativity at work. Using both quantitative and qualitative longitudinal data from the daily diaries of 222 employees in seven companies, we examined the nature, form, and temporal dynamics of the affect-creativity relationship. The results indicate that positive affect relates positively to creativity in organizations and that the relationship is a simple linear one. Time-lagged analyses identify positive affect as an antecedent of creative thought, with incubation periods of up to two days. Qualitative analyses identify positive affect as a consequence of creative thought events, as well as a concomitant of the creative process. A preliminary theory of the affect-creativity cycle in organizations includes each of these links and proposes mechanisms by which they may operate.